2006
DOI: 10.1128/aac.50.5.1900-1902.2006
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Mutations in embB Codon 306 for Prediction of Ethambutol Resistance in Clinical Mycobacterium tuberculosis Isolates

Abstract: We analyzed 159 Mycobacterium tuberculosis isolates (101 ethambutol [EMB]-resistant strains, 33 multidrugresistant but not EMB-resistant strains, and 25 fully susceptible strains) for the presence of mutations in embB codon 306 (embB306). Mutations were detected only in EMB-resistant strains (n ‫؍‬ 69; 68%), thus confirming the significance of embB306 mutations for the prediction of resistance to EMB.Drug-resistant tuberculosis (TB) has become a major public health problem in several regions around the world (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
65
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 14 publications
(21 reference statements)
6
65
1
Order By: Relevance
“…Statistical analysis revealed a significant association between EMB resistance and embB306 mutations in univariate analysis (p < 0.0001), with embB306 mutations the only significant factor in multivariate analysis (p < 0.0001). Thus, our study confirms previous investigations that describe a clear correlation between mutations in emb306 and EMB resistance, 11,21 without any indication of an influence on the resistance to other antituberculous drugs as suggested by other authors. 13,15,16 This high concordance between both assays was, however, determined only after repeating conventional drug susceptibility testing, pointing to problems with conventional diagnostics of EMB resistance.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Statistical analysis revealed a significant association between EMB resistance and embB306 mutations in univariate analysis (p < 0.0001), with embB306 mutations the only significant factor in multivariate analysis (p < 0.0001). Thus, our study confirms previous investigations that describe a clear correlation between mutations in emb306 and EMB resistance, 11,21 without any indication of an influence on the resistance to other antituberculous drugs as suggested by other authors. 13,15,16 This high concordance between both assays was, however, determined only after repeating conventional drug susceptibility testing, pointing to problems with conventional diagnostics of EMB resistance.…”
Section: Resultssupporting
confidence: 93%
“…9 However, if clinical isolates are considered, the percentage of EMB resistant strains which show mutations in embB306 ranges from 30 to 68%. 10,11 Additionally, a number of recent investigations described the occurrence of embB306 mutations in EMB susceptible strains, [12][13][14] and several studies reporting an association with broad drug resistance rather than with EMB resistance alone. 15,16 These contradictory results cast doubt on the potential use of embB306 mutations as molecular markers for predicting EMB resistance in clinical isolates.…”
Section: Introductionmentioning
confidence: 99%
“…Shen et al (6), Plinke et al (3) and numerous authors have exclusively evaluated mutations of this gene in the clinical strains by examining codon embB306. Therefore, study of codon embB497 is neglected with the aim of reducing further simplification of the procedure, and making it possible to perform routinely.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, culture results do not comply fully with the molecular results (determine the occurrence of mutations with low sensitivity, besides high specificity). The precision of determining resistant strains by molecular method has been always debated in previous research (3)(4)(5)(6)11). In most of the studies conducted by other researchers, no mutation in sensitive strains was found (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation